Angle consistency for registration between catadioptric omni‐images and orthorectified aerial images. Issue 4 (1st June 2013) - Xu, Wei; Chen, Wang; Zhang, Jianguo; Zhang, Maojun
Abstract : Registration between catadioptric omni‐images and orthorectified aerial images is the key step to integrate them to achieve three‐dimensional urban construction. This problem becomes very challenging because of the non‐linearity of the imaging model of catadioptric omni‐cameras. In this study, the authors attempt to address this problem. The authors first study the properties of horizontal line structure under catadioptric omni‐cameras to prove and extend the theorem of catadioptric distance, and then present angle consistency of horizontal lines between a catadioptric omni‐image and an orthorectified aerial image. The authors further employ them to achieve registration between catadioptric omni‐images and orthorectified aerial images. To the best of authors' knowledge, this study has not been done before. Experimental results on both simulated data and real scene images confirm the effectiveness of this approach.